The effect of capacity building training programmes on municipal practitioners in selected municipalities within the Capricorn District Municipality, Limpopo Province - Ndou, Siphiwe Davidson (University of Limpopo, 2015)
Local governments are obliged by the Constitution of South Africa to deliver services and development to local communities in their demarcated areas. This constitutional mandate comes at a time where South African government entered into a new regime of government indebted to fix the ill of the Apartheid systems. The government of the post-1994 had to eradicate the inequality offspring of segregation policies of the past that resulted in most of the black communities without access to decent local government services and systems. The provision of services by local government became constrained by skills gaps and distribution across a wider community that had to be included in cascading services. The question of capacity in local government formed a critical part of the transformation of government in South Africa. Never the less local government has been swept by service delivery protest since the 2004 with a sharp increase from 2008 till current. Further pressures that indicate capacity challenges are with the inability of municipalities to deal healthy with financial resource. This challenged is confirmed by the steady poor reports by the auditor general year-in-year-out. These challenges exist where there is a concentrated financing reservations and advocacy of capacity building training programmes, which in turn shows to be failing to address capacity challenges in local government. The study investigated the effects of capacity building training programmes on municipal practitioners in selected municipalities within the Capricorn District Municipality, Limpopo province. The focus of the study is to establish the implication of capacity building training programmes on the capacity of officials to discharge their official duties in the municipalities. The study also dealt with the need for a methodological model that could be used to develop capacity building training programmes. Competency-Based Training was studied in pursuit for recommendation as a model for capacity building in local government. The study was grounded within the boundaries of the systems thinking with bias to the complex systems thinking. To fulfil the purpose of the study data was collected through qualitative and quantitative methods. Analyses were made using the Statistical Package for Social Science. The findings of the study revealed that though there are positive effects of capacity building training programmes in local government there is much to be done especial the alignment of capacity with the strategic positioning of the participating municipalities.
Thesis (MPA. (Public Administration)) -- University of Limpopo, 2015
Keywords: Local government; South African Constitution; Service delivery; Apartheid system; Capacity building training programmes; Local municipality; Employees -- Training of